2010
DOI: 10.3340/jkns.2010.48.1.66
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Experience of Neglected Lower Cervical Spine Fracture in Patient with Ankylosing Spondylitis

Abstract: J Korean Neurosurg Soc 48 : [66][67][68][69] 2010 The management of lower cervical fractures in patients with ankylosing spondylitis (AS) differs from normal cervical fractures. Patients with AS are highly susceptible to extensive neurologic injuries and spinal deformities after cervical fractures from even minor traumatic forces. These injuries are uniquely complex, require careful imaging assessment, and aggressive surgical management to optimize spinal stability and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Elderly patients with AS and acute fractures have been shown to have better results when treated surgically [ 4 ]. Caron et al [ 2 ], in their large retrospective review, showed a mortality rate of 51% in the nonoperative group versus 23% in the operative group with age >70 being a major risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients with AS and acute fractures have been shown to have better results when treated surgically [ 4 ]. Caron et al [ 2 ], in their large retrospective review, showed a mortality rate of 51% in the nonoperative group versus 23% in the operative group with age >70 being a major risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, Powell et al [20] in 1989 suggested that the existence of even a single normal vertebral body between the fractured vertebrae could be considered as a noncontinuous multiple vertebral fracture. The incidence of noncontinuous multiple vertebral fractures has been reported to range from 1.6% to 16.7% [7,8,23].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with noncontinuous multiple vertebrae fractures, the primary fracture site is easily diagnosed clinically and radiologically, but the diagnosis of secondary fractures often tends to be delayed. According to some reports, it took 2.8 to 52.6 days to diagnose the secondary fracture site [8,13]. The reasons for the delayed diagnosis of other vertebral fractures are as follows [13,20].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these conservative treatments were associated with significant problems: risk of skin ulcerations, local septic, and respiratory problems, worsening of the regional kyphosis with loss of reduction, risk of non-union because of the shearing forces on the fracture site [19], and risk of neurological aggravation [20]. Overall, we suggest that conservative treatment only may not be suitable for this kind of fracture, particularly, in patients with severe neurological symptoms and unstable patterns such as type III and subtypes B and C. Furthermore, we strongly recommend surgery for a cervical fracture in AS, which is presently widely used [11,[21][22][23][24][25][26]]. e procedures had been described including anterior approach, posterior approach, and combined approach, and the surgical procedures in relation to classification were analyzed as described below.…”
Section: Choice Of Treatment Related To Different Fracturementioning
confidence: 94%